2022
DOI: 10.1111/ger.12634
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of tooth loss in Brazilian older adults: An 8‐year follow‐up

Abstract: Objective To investigate the risk factors for tooth loss after 8 years among community‐dwelling older adults in a southern Brazilian city. Methods In 2004, 388 dentate community‐dwelling older adults from Carlos Barbosa, southern Brazil, were selected using simple random sampling. In 2012, the follow‐up consisted of 199 (51.3%) participants. Data collection comprised an interview with data about socio‐demographic, behavioural and access to services and an oral examination. The outcome variable of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…. The covariates were selected based on a review of the subject literature [7][8][9][10][11][12][13][14][15][16][17][18] and a previous study [21]. The data were analysed using STATISTICA 13.3 software (STATSOFT, PL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. The covariates were selected based on a review of the subject literature [7][8][9][10][11][12][13][14][15][16][17][18] and a previous study [21]. The data were analysed using STATISTICA 13.3 software (STATSOFT, PL).…”
Section: Discussionmentioning
confidence: 99%
“…Its direct causes are usually untreated caries and periodontal diseases [7][8][9]. The prevalence of tooth loss and the factors that directly determine it depend largely on economic development, access to dental care, social factors, and lifestyle, which is why they may differ between countries and regions [8][9][10][11][12][13][14][15]. Loss of teeth not only reduces the effectiveness of mastication but also contributes to a limitation, or even complete elimination, of hard products from the diet (e.g., nuts and some raw fruits and vegetables), signi cantly reducing the nutritional value of food [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is relevant to mention, however, that both age-standardized prevalence and years lived with disability for tooth loss have decreased in highincome countries, while an increase was observed in the lower ones, suggesting that this current social pattern will reverse if this trend continues. 3 Indeed, findings from middle-and low-income countries have shown that tooth loss is socioeconomically patterned 54,55 and increases with age, 56 meaning that the most disadvantaged and older have the highest extent of tooth loss. In this respect, understanding the forces behind trends in tooth loss inequalities is critical for tackling health disparities.…”
Section: Public Health Implicationsmentioning
confidence: 99%